TEACHING SPEAKING SKILLS THROUGH TASK-BASED APPROACH IN EFL CLASSROOMS (Academicia Globe: Inderscience Research, 2022)
Nowadays, learning English language is becoming easier and easier, though speaking is still remaining as one of the most challenging skills to acquire. While most students do not have proper knowledge of the necessary skills to improve speaking, some just lack some psychological things to have.The main aim of this article is to find the most effective solution to this problem and show why this solution could actually be an effective one. I personally and profoundly believe that task-based approach what makes the learning process easier and better. All the reasons of this view will be provided on this paper.